A QUALITATIVE STUDY ON THE EFFECTIVENESS OF TEACHER-STUDENT COMMUNICATION STRATEGIES IN ASYNCHRONOUS ONLINE TEACHING: STUDENT PERSPECTIVES ON SELF-ESTEEM AND ACADEMIC PERFORMANCE - Mathur, Bhawna; Shukla, Neetu Mishra; Kumar, Indu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The transformative influence of technology has significantly altered the global educational landscape since the 1990s. Notably, the integration of online learning has become pervasive across diverse learning environments, encompassing formal and informal settings, academic and non-academic spheres, as well as residential and remote contexts (Elaish et al., 2019; Garcia et al., 2018; Barrot et al.,2021). The increasing adoption of e-learning tools by educational institutions, teachers, and students has facilitated interactive instructional methods, seamless resource distribution, and enhanced student collaboration and engagement. The evolution of distance learning has been influenced by economic shifts, organizational demands, and the explosive expansion of the Internet. This paradigm shift in education transcends traditional teaching methods, allowing virtual communication between students and educators in a classroom setting without physical encounters. Technological advancements have brought about transformative changes in education, ushering in online and hybrid curricula.